Effects of Gd2O3 and MgSiN2 sintering additives on the thermal conductivity and mechanical properties of Si3N4 ceramics. Issue 3 (4th December 2022) - Fu, Shi; Yang, Zengchao; Li, Honghua; Wang, Liang; Li, Yong; Li, Jiangtao
Abstract: Si3 N4 ceramics were prepared by gas pressure sintering at 1900°C for 12 h under a nitrogen pressure of 1 MPa using Gd2 O3 and MgSiN2 as sintering additives. The effects of the Gd2 O3 /MgSiN2 ratio on the densification, microstructure, mechanical properties, and thermal conductivity of Si3 N4 ceramics were systematically investigated. It was found that a low Gd2 O3 /MgSiN2 ratio facilitated the thermal diffusivity of Si3 N4 ceramics while a high Gd2 O3 /MgSiN2 ratio benefited the densification and mechanical properties. When the Gd2 O3 /MgSiN2 ratio was 1:1, Si3 N4 ceramics obtained an obvious exaggerated bimodal microstructure and the optimal properties. The thermal conductivity, flexural strength, and fracture toughness were 124 W·m −1 ·k −1, 648 MPa, and 9.12 MPa·m 1/2, respectively. Comparing with the results in the literature, it was shown that Gd2 O3 ‐MgSiN2 was an effective additives system for obtaining Si3 N4 ceramics with high thermal conductivity and superior mechanical properties.